Perancangan Enterprise Architecture di PT.BMP Menggunakan Metode Enterprise Architecture Planning (EAP) - Imelda Yunike Sari; Lily Puspa Dewi; Alexander Setiawan (Jurnal Infra, 2017)
PT.BMP is a company engaged in the production of primary goods made from plastic that produce plastic door. The company uses the Bee-accounting software to process the purchase, production, sales, and finance as well as Solution Finger Print software for data collections and employee payroll. There are still some manual processes such as hiring employees, maintain the engine, engine repair reports, creation of SPK, and recording quality control. For the calculation of sales commissions still manually because the sales data and employee data is not integrated.Therefore, the analysis and enterprise architecture design creation with enterprise architecture planning method (EAP) for PT.BMP must be formed. The first process to be done is to analyze the business model and the company’s business strategy. Then, make observations regarding the company's information technology today, its problems and needs of the company in the future. After that, the design of data architecture, application architecture, and technology architecture can be make.The result of data architecture is a sub-system of purchasing, production, sales, finance and personnel. Applications that include to Key Operational is purchase information system, production information system, sales information system, financial information systems, and personnel information systems. Applications that included support is a GPS System Vehicle. Technology architecture use a client / server architecture and service oriented architecture pattern.